2015
DOI: 10.1108/tldr-08-2014-0028
|View full text |Cite
|
Sign up to set email alerts
|

Narrative therapy in a learning disability context: a review

Abstract: Purpose – Narrative therapy is aligned with government priorities for learning disabilities as it promotes inclusion and seeks to empower. While research on narrative therapy in learning disability services is emerging, it has not been critically evaluated. The purpose of this paper is to identify, summarise and critique the extant literature that has explored narrative therapy for adults with learning disabilities, and consider the implications for research and clinical practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The findings indicated that in their new homes, people were given opportunities to widen out the stories they and others held about them, rather than focus on a problem‐saturated narrative (McParland, ). Guidance on the use of Positive Behavioural Support (PBS) to work with behaviours which challenge (NICE, ) similarly emphasises proactive improvements to the person's environment and daily life as a way of situating such behaviours within environmental contexts rather than relying on purely internalised explanations (Banks et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that in their new homes, people were given opportunities to widen out the stories they and others held about them, rather than focus on a problem‐saturated narrative (McParland, ). Guidance on the use of Positive Behavioural Support (PBS) to work with behaviours which challenge (NICE, ) similarly emphasises proactive improvements to the person's environment and daily life as a way of situating such behaviours within environmental contexts rather than relying on purely internalised explanations (Banks et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The findings indicated that in their new homes, people were given opportunities to widen out the stories they and others held about them, rather than focus on a problem-saturated narrative (McParland, 2015).…”
Section: Larry: Terriblementioning
confidence: 99%
“…Outcome measurement is challenging within the context of evaluating the tree of life approach and narrative therapy generally, particularly where there is not one specific ‘difficulty’ being addressed and the focus is rather on the ‘thickening’ of positive stories about oneself (McParland, ). This study reports outcomes from only one group with four participants; therefore, caution must obviously be taken in terms of generalisability of any results.…”
Section: Discussionmentioning
confidence: 99%
“…Within this, there are several examples of narrative therapy groups being run to support people with learning disabilities, two of which focus specifically on supporting people to understand and manage the feelings of anger (Baxter & Wilcox, ; Hoole & Morgan, ), and a more recent study outlining a narrative therapy group for people with learning disabilities who are gay, lesbian, bisexual or transgender (Elderton et al ., ). In addition, a recent review of individual narrative therapy for people with learning disabilities also concluded that there was some evidence for its usefulness, particularly in relation to difficulties with anger, but that further larger‐scale research is still required (McParland, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interviewees externalised dementia; this indicates that narrative therapy involving problem externalisation may be a useful approach (White, 1998). There is emerging evidence for adapted narrative therapy with individuals with learning disabilities (McParland, 2015), which may suggest a potential usefulness for those with other cognitive difficulties such as dementia. For those with advanced dementia, emphasising character traits and resources related to sexual orientation could be an alternative to sequential narratives (Young, 2010).…”
Section: Discussionmentioning
confidence: 99%